Penyelesaian Konflik Rusia-Ukraina Dalam Perspektif Hukum Internasional - Octavia, Ardita; Husniyah, Alya (Tirtayasa Journal of International Law, 2023)
The conflict between Russia and Ukraine is the biggest problem facing international relations today. On February 24, 2022, Russia carried out a massive migration by sending missiles to Ukrainian territory, including the capital city of Kiev. In this military operation, the Military Forces were also attacked by Russia. This article aims to examine 1) International Causes and Impacts of the Russia-Ukraine conflict; 2) Analysis of Conflict Resolution Between Russia and Ukraine in the Perspective of International Law. The research method used in this research is normative research, namely collecting data or scientific work according to the research object or library research. The Russian-Ukrainian conflict There are three important geopolitical, demographic and socio-political factors that are the cause. The settlement of disputes between Russia and Ukraine is now ending by force or coercion, where there is no initiative from the two countries to take a peaceful path. There are 3 ways that can be taken to resolve the Russian-Ukrainian war, including negotiations, international organizations, and mediation. This effort can be used as an alternative effort to end the Russia-Ukraine conflict.